Dominica : 2008 Article IV Consultation Staff Report; Staff Supplement; Staff Statement and Public Information Notice on the Executive Board Discussion; 2008 Article IV Consultation-Staff Report; Staff Supplement; Staff Statement, and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
The 2008 Article IV Consultation with Dominica discusses external competitiveness and key policy issues. The real effective exchange rate is broadly in line with macroeconomic fundamentals. Fiscal policy is appropriately focused on reducing high public debt. Plans for developing the tourist sector, including improving air access and roads to tourist attractions, are well advanced and should be financed with a view maintaining the sustainability of public debt. The authorities rightly emphasize improving the business climate, strengthening regulation and supervision of the financial sector, and improving disaster preparedness.